Perioperative and Postoperative Management in Gynecologic Oncologic Patients: A Narrative Review - Nurkulis; Patiyus Agustiansyah (Sriwijaya Journal of Medicine, 2025)
Gynecologic cancers, particularly cervical, ovarian, and endometrial cancers, remain among the leading causes of mortality in women. Surgery, the cornerstone of treatment, is often associated with significant perioperative risks, necessitating careful evaluation and management to optimize outcomes. This review analyses perioperative and postoperative factors influencing morbidity and mortality in gynecologic oncology and evaluates the role of Enhanced Recovery After Surgery (ERAS) protocols in improving outcomes. A literature search by Google Scholar, PubMed, and ScienceDirect identified eight relevant evidence-based studies published within the last decade. Findings demonstrate that ERAS accelerates recovery, reduces complications, and lowers healthcare costs. Key components—such as patient education, multimodal analgesia, bowel function optimization, and early mobilizations significantly enhance postoperative recovery. Patients with comorbid endocrine, cardiovascular, renal, and electrolyte disorders require intensive monitoring and tailored management to prevent complications. Overall, the application of ERAS in gynecologic oncology improves recovery, reduces morbidity, and enhances quality of life, particularly when combined with vigilant monitoring in high-risk patients.